2023
DOI: 10.3390/plants12102011
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Proteins and Peptides to the Impact of a Soy Protein Isolate on Oxidative Stress and Inflammation-Associated Biomarkers in an Innate Immune Cell Model

Abstract: The innate and adaptative immune systems are involved in the regulation of inflammatory and oxidative processes and mediators such as reactive oxygen species (ROS) and nitric oxide (NO). The exacerbated action of these players results in an oxidative stress status and chronic inflammation, which is responsible for the development of non-communicable diseases (NCDs). By modulating these mediators, bioactive compounds in food can exert a key role in the prevention of several NCDs. Among these compounds, soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In Caco-2 cells, the antioxidant effect of this peptide was also demonstrated, reducing ROS levels in a dose-dependent manner, with a reduction of 62.7% at 25 µM [35]. Recently, we demonstrated that a soybean protein isolate reduced ROS generation in lipopolysaccharide (LPS)-challenged macrophages RAW264.7, being medium and low-molecular weight peptides the main responsible for the observed effects [36]. The discrepancies between these studies and our current results could be due to different factors such as the type of cell line used, the concentration of lunasin or antioxidant peptides present in LSE or the presence of other compounds in our extract that could antagonize the effect of lunasin and other antioxidant compounds [19,37].…”
Section: Antioxidant and Anti-inflammatory Activity Of Lsementioning
confidence: 86%
“…In Caco-2 cells, the antioxidant effect of this peptide was also demonstrated, reducing ROS levels in a dose-dependent manner, with a reduction of 62.7% at 25 µM [35]. Recently, we demonstrated that a soybean protein isolate reduced ROS generation in lipopolysaccharide (LPS)-challenged macrophages RAW264.7, being medium and low-molecular weight peptides the main responsible for the observed effects [36]. The discrepancies between these studies and our current results could be due to different factors such as the type of cell line used, the concentration of lunasin or antioxidant peptides present in LSE or the presence of other compounds in our extract that could antagonize the effect of lunasin and other antioxidant compounds [19,37].…”
Section: Antioxidant and Anti-inflammatory Activity Of Lsementioning
confidence: 86%
“…The remarkable potential of nutraceuticals extends far beyond their actions; it resides in their unique ability to orchestrate a symphony of benefits, harmoniously targeting multiple intricate pathways implicated in oxidative stress and inflammation [ 80 , 81 , 82 ]. The advent of personalized medicine has introduced a highly promising avenue for optimizing nutraceutical therapy within the realm of these medical conditions [ 83 ].…”
Section: Challenges In Metabolic Disorders and Nutraceuticals As A No...mentioning
confidence: 99%
“…In terms of the functionality of bioactive components, this SI reported several interesting applications, with one of them being focused on proteins and peptides (the only paper in this Issue containing these bioactive compounds) derived from a soy protein isolate [14]. Soybean proteins and peptides, such as lunasin, have been considered promising bioactive compounds in the regulation of inflammatory and oxidative processes and mediators, such as reactive oxygen species (ROS) and nitric oxide (NO).…”
Section: An Overview Of the Simentioning
confidence: 99%